Bioproducts From Euglena gracilis: Synthesis and Applications - Gissibl, Alexander; Sun, Angela; Care, Andrew; Nevalainen, Helena; Sunna, Anwar (Frontiers in Bioengineering and Biotechnology, 2019)
In recent years, the versatile phototrophic protist Euglena gracilis has emerged as an interesting candidate for application-driven research and commercialisation, as it is an excellent source of dietary protein, pro(vitamins), lipids and the β-1,3-glucan paramylon only found in euglenoids. From these, paramylon is already marketed as an immunostimulatory agent in nutraceuticals. Bioproducts from E. gracilis can be produced under various cultivation conditions discussed in this review, and their yields are relatively high when compared with those achieved in microalgal systems. Future challenges include achieving the economy of large-scale cultivation. Recent insights into the complex metabolism of E. gracilis have highlighted unique metabolic pathways, which could provide new leads for product enhancement by genetic modification of the organism. Also, development of molecular tools for strain improvement are emerging rapidly, making E. gracilis a noteworthy challenger for microalgae such as Chlorella spp. and their products currently on the market.